Cryopreservation of Brown Trout (Saltno trutta fario) Sperm: The Influence of Extender Composition and Fertilization Procedure - A., Gopalakrishnan; K.L., Thakur; A.G., Ponniah; K., Kumar; R., Dayal (Fishery Technology, 2025)
Seven extenders were tested to check their relative efficiency in cryopreserving the milt of brown trout (Salmo trutta fario). Hatching rates equal to that of control (p > 0.05) were obtained when a cryodiluent containing egg yolk (2%) and dimethylsulphoxide (10%) was used. Removal of coelomic fluid prior to the addition of thawed milt and addition of 5 mM theophylline to the "Dexter" solution enhanced the hatching percentage. The sperm density varied from 9.83 to 18.41 x 109 sperms/ml.